TEACHING OF CULTURE AS AN INTEGRAL PART OF FOREIGN LANGUAGE EDUCATION - Nurkenova S.S., Nurkenova S.S.; Kemеlbekova E.А. Kemеlbekova E.А.; Seitesheva T.A., Seitesheva T.A. (Рroblems of engineering and professional education, 2023)
This article aims at considering various views on the relationship of culture with language and what role it plays in teaching and learning English as a foreign language